The activity of a herbal medicinal product of Phyllanthus niruri and Silybum marianum powdered extracts (Heptex®) in patients with apparent risk factors for nonalcoholic steatohepatitis: a phase II, multicentered, randomized, double-blind, placebo-controlled clinical trial - Mohamed Kamal Shaker; Mohamed Hassany; Basem Eysa; AbdulMoneim Adel; Ahmed Zidan; Shahnaz Mohamed (BMC Complementary Medicine and Therapies)
Abstract Background Nonalcoholic steatohepatitis (NASH) is a severe form of nonalcoholic fatty liver disease (NAFLD) characterized by damage and inflammation of hepatocytes. Some medicinal plants have shown antioxidant and anti-inflammatory effects on liver cells. We aimed to investigate the hepatoprotective effect of Heptex® capsules containing 200 mg of Dukung Anak (a powdered extract from aerial parts of Phyllanthus niruri) and 100 mg of Milk Thistle (a powdered extract from fruits of Silybum marianum) in patients with an apparent risk factor for NASH. Methods This was a phase II, randomized, double-blind, placebo-controlled, three-arm, interventional clinical trial. Patients were randomized in a 1:1:1 ratio to receive placebo, low dose (one capsule) of Heptex®, or high dose (two capsules) of Heptex®. After 36 weeks, liver enzymes, Fib-4 score, lipid profile, CAP score, and kPa score were evaluated. Patients were monitored for safety throughout the treatment duration. Results A total of 146 patients were enrolled in the study. A significant decrease was observed in ALT levels in the low-dose group (57 IU/L to 40 IU/L, p = 0.026) and the high-dose group (61 IU/L to 47.5 IU/L, p < 0.0001) and in AST levels in the high-dose group (43.5 IU/L to 32 IU/L, p = 0.001), with no significant difference between the relative percent change in ALT (p = 0.465) or AST (p = 0.632) between the three groups. No significant difference was revealed between the three groups regarding the median change in Fib-4 score at the end of treatment (p = 0.985). No significant change in the lipid profile was observed in any of the three groups except for the total cholesterol level, which significantly decreased from 210 IU/L to 187 IU/L, p = 0.031 in the low-dose group. Conclusion Heptex® capsules were safe and well tolerated over a treatment period of 36 weeks. However, the hepatoprotective effect in patients at risk of NASH still needs further assessment using more accurate investigation tools, a larger sample size, and/ or higher doses of the combination. Trial registration Retrospectively registered (registration date: 25/04/2022; trial registration number: NCT05343780)